Investment management & recovery process of Social Islami Bank Limited. A report on the corporate branch of Brahmanbaria - MD., Al-Razi (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.